Experiences of stigma in healthcare settings by people living with HIV in Ireland: a qualitative study. Issue 9 (1st September 2020) - Vaughan, Elena; Power, Martin; Sixsmith, Jane
ABSTRACT: Stigma in healthcare settings remains a barrier to accessing screening, treatment and care for HIV and is a driver of the global HIV epidemic. This study examined the stigma experiences in healthcare settings of people living with HIV (PLHIV) in Ireland. Semi-structured interviews were carried out with 4 women and 10 men living with HIV. Data were analysed using a Directed Content Analysis approach to assess experiences of enacted, anticipated and internalised stigma. The findings indicate experiences of enacted, anticipated and internalised stigma were common. A further finding of spatial stigma was also uncovered. Analysis showed these experiences impacted participants' engagement with care and affected health-seeking behaviours and treatment adherence. The results suggest stigma experienced in healthcare settings may impact negatively on health outcomes.